Herb Composites in Medicinal Applications: Synergistic Formulations and Historical Foundations - Zainulabdeen, Khalid; W. Younus, Reem; Ismael, Shams; Hadi Mohammed, Asmaa; Bufaroosha, Muna; Al-Sarraj, Emad (Al-Nahrain Journal of Science, 2025)
Herbal composites, or polyherbal formulations, have been used in traditional medicine practices such as Traditional Chinese Medicine (TCM) and Ayurveda, leveraging the synergistic interactions among multiple plant species to enhance therapeutic outcomes. This review aims to summarize the current state of knowledge on herbal composites, exploring their mechanisms of action, potential benefits, and challenges associated with their development and clinical validation. The results highlight the synergistic interactions among herbs, including pharmacokinetic interactions where one herb influences the absorption or metabolism of another, and pharmacodynamic interactions where compounds target different biological pathways, leading to improved efficacy and bioavailability, as well as enhanced safety profiles. In conclusion, despite their potential, herbal composites face significant challenges, including the standardization of phytochemical profiles and concerns regarding herb-drug interactions. Therefore, it is recommended that rigorous clinical validation through larger, multi-center randomized controlled trials is essential to confirm the safety and efficacy of herbal composites, and that standardization of phytochemical profiles and careful evaluation of herb-drug interactions are also crucial to enhance the reliability of these formulations, ultimately allowing herbal composites to become a more integral part of modern medicine, offering new treatment options for patients.